2012
DOI: 10.1007/s11307-012-0582-y
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of [18F]Mefway Biodistribution and Dosimetry Based on Whole-Body PET Imaging of Mice

Abstract: Purpose [18F]Mefway is a novel radiotracer specific to the serotonin 5-HT1A receptor class. In preparation for using this tracer in humans, we have performed whole-body PET studies in mice to evaluate the biodistribution and dosimetry of [18F]Mefway. Methods Six mice (three females and three males) received IV injections of [18F]Mefway and were scanned for 2 h in an Inveon-dedicated PET scanner. Each animal also received a high-resolution CT scan using an Inveon CT. The CT images were used to draw volume of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 13 publications
2
22
0
Order By: Relevance
“…At the end of the respective measurement, the values decreased significantly for the liver (mice, 0.05 6 0.02; piglets, 5.4 6 2.1; humans, 8.4 6 1.2) and kidneys (mice, 0.01 6 0.003; piglets, 1.4 6 0.3; humans, 1.4 6 0.3). These organs are the most highly exposed in all investigated species, with organ doses comparable to those of other 18 F-labeled tracers (e.g., 18 F-mefway, 18 F-nifene) (13,14) as well as to the 11 C-labeled 11 C-WAY (15). Figure 6 shows a summary of all ODs for the 3 investigated species.…”
Section: Discussionmentioning
confidence: 84%
“…At the end of the respective measurement, the values decreased significantly for the liver (mice, 0.05 6 0.02; piglets, 5.4 6 2.1; humans, 8.4 6 1.2) and kidneys (mice, 0.01 6 0.003; piglets, 1.4 6 0.3; humans, 1.4 6 0.3). These organs are the most highly exposed in all investigated species, with organ doses comparable to those of other 18 F-labeled tracers (e.g., 18 F-mefway, 18 F-nifene) (13,14) as well as to the 11 C-labeled 11 C-WAY (15). Figure 6 shows a summary of all ODs for the 3 investigated species.…”
Section: Discussionmentioning
confidence: 84%
“…(4)) showed that the effective doses calculated from rat data were overestimated compared to those measured in nonhuman primates [22]. On the other hand the results of our previous work [23] in which we extrapolated the mouse dosimetry of the 5-HT 1A tracer [ 18 F]Mefway to human suggested that the urinary organs (bladder and kidneys) doses derived from the mouse model were underestimated.…”
Section: Discussionmentioning
confidence: 99%
“…Based on biodistribution data, the excretion for [ 18 F]Mefway were mainly through the gastrourinary tract because of the radioactivity preceding pattern from the kidney to the urinary bladder and the remarkable uptake in the urinary system compared with the digestive system. The estimated radiation dose of 40.23 μSv/MBq from the human subjects is 3.3 times larger than the previous preclinical prediction results from the mice (11.3 or 12.1 μSv/MBq) [17]. In addition, little uptake in the bone indicates that [ 18 F]Mefway has metabolic stability against in vivo defluorination in humans.…”
Section: Discussionmentioning
confidence: 66%